Predictors of the Actual Final Grade in Mathematics Subject of International Baccalaureate Diploma Programme Students in Surabaya, Indonesia - -, Arnel Macabuag; -, Edwin D. Ibañez (International Journal For Multidisciplinary Research, 2024)
This study tried to investigate what are the possible indicators of the performance of International Baccalaureate Diploma Programme Students taking Mathematics Standard Level in an international school in Surabaya. The research made use of secondary data gathered from the school such as the scores of the students and together with their profile. The data covered academic years 2014 – 2019. Other than the secondary data and information gathered from the administration office and curriculum coordinators, The researcher also gathered the progress scores of the students from their subject teachers, one of whom is yours truly. Descriptive-correlational research design was used to analyze the data. Data collected were analyzed and interpreted using frequency, percentage, mean, standard deviation and Pearson Product Moment Correlation. One-way Analysis of Variance was also used to check if there is significant difference among mock exam score for Predicted Grade (PG), General Point Average (GPA) and final grades. Among the socio-demographic characteristics of the respondents, only gender significantly related to the final grade. Both GPA and mock exam predicted grades indicated that both grades have strong significant relationship to the final external examination grades of the students.